Design and Impedance Modeling of a Compact Sequentially Rotated Quasi-Lumped Antenna Array for Wi-Fi Applications - Yazeed M. I. Qasaymeh (International Journal of Antennas and Propagation)
In this study, a miniaturized 2 × 2 sequentially rotated (SR), circularly polarized (CP), and quasi-lumped antenna array that resonates in the IEEE 802.11a band is introduced. The shorting pins technique is implemented to achieve circular radiation patterns, and the resonating elements are excited using a SR quarter-wavelength feeding network. A resonance model of the four radiating elements array is postulated to give a physical insight into the relative dimensions and to allow for a study of the resonance characteristics and the effect of the shorting pins. An antenna model is simulated, fabricated, and measured to authenticate this arrangement, giving results of |S11| < −10 dB and axial ratio (AR) < 3 dB for bandwidths of 3.85% (5.645–5.867 GHz) and 1.54% (5.77–5.86 GHz) for right-hand circular polarization (RHCP). The size of the antenna array structure is 0.696λ0×0.599λ0×0.0157λ0 at a center frequency of 5.8 GHz.